Changes in the ascorbate system in the response of pumpkin (Cucurbita pepo L.)roots to aluminium stress - Dipierroa, N.; Mondellib, D.; Paciollaa, C.; Brunettib, G.; Dipierroa, S.
The involvement of the ascorbate (AsA)system in the response of pumpkin (Cucurbita pepo L.)roots to aluminium stress was studied. The treatment of 5-day-old pumpkin seedlings with 50 mM aluminium sulphate resulted in approximately 60
Keywords: ALUMINIUM; ASCORBATE; ASCORBATE PEROXIDASE; CUCURBITA PEPO; HYDROGEN PEROXIDE; OXIDATIVE STRESS; TOXICITY